مستقبل الدور الروسي في منطقة شرق المتوسط (قضايا سياسية, 2022)
The study of the future of the Russian role in the eastern Mediterranean region is one of the important studies, because it deals with understanding the role of a country that has its position in the international arena and represents one of the major powers in the international system in a region that is considered one of the vital and strategic areas. Because Russia was able to regain its regional and international role and influence, and it was also able to return as a major actor in the international system,Its role in the international and regional environment continues to evolve, and it has also been able to prove that it is a reliable ally through its role in the Syrian events in addition to its success in forming strong relations with the countries of the region and building economic relations in the field of energy and investments, and Russia knows very well that it is It cannot confront the United States of America and it does not wish to enter into a conflict with it because it knows that its capabilities may not allow it to do so. Therefore, it has dealt with the issues of the Eastern Mediterranean region without bypassing the interests of the United States of America.